(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article analyzes the special characters of films directed by Melis Abzalov, which has a significant role in the development of the comedy genre in Uzbek cinema, and also examines the artistic and ideological features of the film, the achievements of its creative components and the significance in our modern cinema.